2017
DOI: 10.1016/j.jacbts.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Arrhythmia by Enhancing Mitochondrial Ca2+ Uptake in Catecholaminergic Ventricular Tachycardia Models

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 45 publications
2
66
1
Order By: Relevance
“…In this study, we present evidence that the efsevin‐induced change in gating facilitates transfer of Ca 2+ from the SR into mitochondria. Interestingly, we never observed an involvement of the drug in apoptosis, neither in this study nor in previous studies (Schweitzer et al, 2017; Shimizu et al, 2015) despite a previously identified isoform‐specific role for VDAC2 in apoptosis through recruitment of Bax (Lauterwasser et al, 2016; Ma et al, 2014). Efsevin could thus serve as a tool to dissect these functions in future studies.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…In this study, we present evidence that the efsevin‐induced change in gating facilitates transfer of Ca 2+ from the SR into mitochondria. Interestingly, we never observed an involvement of the drug in apoptosis, neither in this study nor in previous studies (Schweitzer et al, 2017; Shimizu et al, 2015) despite a previously identified isoform‐specific role for VDAC2 in apoptosis through recruitment of Bax (Lauterwasser et al, 2016; Ma et al, 2014). Efsevin could thus serve as a tool to dissect these functions in future studies.…”
Section: Discussioncontrasting
confidence: 92%
“…It is thus conceivable that despite the ubiquitous expression of VDACs in the body, efsevin‐mediated effects are most pronounced or even limited to cardiomyocytes due to the specialized role of VDAC2 in this tissue. This effect might also explain the lack of major side effects that were observed previously in translational models (Schweitzer et al, 2017). However, future studies are needed to evaluate the role of the efsevin‐mediated effects on other VDAC2‐mediated effects like apoptosis or regulation of bioenergetics (for a review, see Naghdi & Hajnóczky, 2016).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Authors concluded that this mechanism could explain the efsevin-induced facilitated transfer of calcium from the sarcoplasmic reticulum into mitochondria in zebra fish. Interestingly, in these studies, efsevin has not been observed to be involved in apoptosis (Schweitzer et al, 2017;Wilting et al, 2020) despite the accepted role of VDAC2 in apoptosis through recruitment of Bax or Bak (Cheng et al, 2003;Chin et al, 2018).…”
Section: Screening Non-polar Compounds For Vdac Functional Controlmentioning
confidence: 88%
“…Efsevin was demonstrated to bind to zebra fish VDAC2 (zfVDAC2) by an affinity pulldown assay (Shimizu et al, 2015). Efsevin is thought to enhance mitochondrial uptake of calcium through VDAC2, thereby preventing calcium accumulation in the cytosol (Schweitzer et al, 2017). Lately, using an in vitro system of reconstituted zfVDAC2 channels, Wilting et al (2020) found that efsevin promotes channel closure and shifts its selectivity toward less anionic thus, according to the previous studies (Rostovtseva et al, 2005;Tan and Colombini, 2007), ultimately causing an increase of VDAC2 permeability for calcium.…”
Section: Screening Non-polar Compounds For Vdac Functional Controlmentioning
confidence: 91%